Epistemology, ontology and challenges of law - Lavado Mallqui, Lucas (2019)
This article covers three parts: the first, some epistemological proposals about the theories, with emphasis on the theory of law taking into account its structure and the roles it fulfills mainly with respect to research. The second, includes some details about the ontology of legal norms compatible with epistemology. Third, ithighlights the challenges of law in the current scenario, emphasizing interdisciplinarity, the review of research methodology and finally the role of law schools regarding the efficiency of justice in Peru.